In vitro biological properties and characterization of nanosilver coated cotton fabrics – An application for antimicrobial textile finishing. (February 2016) - Balakumaran, M.D.; Ramachandran, R.; Jagadeeswari, S.; Kalaichelvan, P.T.
Abstract: The aim of this study was to evaluate the antibacterial and antifungal activities of cotton fabrics coated with silver nanoparticles (AgNPs). Stable AgNPs synthesized using Aspergillus terreus were characterized using UV–Vis. spectrophotometer, HR-TEM, XRD, and EDX. The synthesized AgNPs were 8–20 nm in size. In agar based diffusion and parallel streak methods, AgNPs coated cotton fabrics exhibited broad spectrum antibacterial activity against all pathogens tested. Importantly, AgNPs coated fabrics provided excellent laundering durability with pronounced antibacterial activity even after 15 wash cycles. The extent of release of silver ions from AgNPs coated fabrics into artificial sweat was studied using four different formulations (AATCC, ISO, and EN standards) with a pH range of 4.0–8.0. The maximum release of silver ions (31.71 mg/kg) was observed at pH 4.3 (AATCC formulation) while the minimum level of release (12.27 mg/kg) occurred at pH 8.0 (ISO formulation). HR-SEM micrographs of cotton fabrics coated with AgNPs exhibited a rough surface and the presence of nanoparticles on the cotton surface was also observed. Thus, the results of the present study clearly suggest that AgNPs synthesized using a green chemical technology could be considered in the development of antimicrobial textile finishes. Graphical abstract: Highlights: Antimicrobial cotton fabrics were prepared by simple pad-dry-cure method. AgNPs coated cotton fabrics showed broad spectrum antibacterial activity. AgNPs coated fabrics showed good laundering durability even after 15 wash cycles. The release of silver ions from AgNPs coated fabrics was analyzed. Presence of AgNPs on cotton fabrics was confirmed by HR-SEM and EDX analyses.